2019
DOI: 10.1088/1361-648x/ab0f0d
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of intrinsic superconductivity below 1.178 K in the topologically non-trivial semimetal state of CaSn3

Abstract: Topological materials which are also superconducting are of great current interest, since they may exhibit a non-trivial topologically-mediated superconducting phase. Although there have been many reports of pressure-tuned or chemical-doping-induced superconductivity in a variety of topological materials, there have been few examples of intrinsic, ambient pressure superconductivity in a topological system having a stoichiometric composition. Here, we report that the pure intermetallic CaSn3 not only exhibits t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 45 publications
6
12
1
Order By: Relevance
“…2b and c, nodes in the beating patterns produce π phase shifts in the oscillations. While the frequencies of F α , F β , and F γ are in good agreement with those previously reported [10], F δ that is prominent above 30 T (or 1/B < 0.033 T −1 ) is newly identified by the present work.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…2b and c, nodes in the beating patterns produce π phase shifts in the oscillations. While the frequencies of F α , F β , and F γ are in good agreement with those previously reported [10], F δ that is prominent above 30 T (or 1/B < 0.033 T −1 ) is newly identified by the present work.…”
supporting
confidence: 93%
“…The observed frequencies F are associated with ex- lar to the previous report [10]. The dHvA frequencies extracted from the FFT analysis exhibit nearly isotropic angular dependence for the α, β, γ, and δ orbits, as shown in fig.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Up to now, the physical properties of ASn 3 have been less studied as compared with LnM 3 . The recent studies on CaSn 3 have revealed it as a weakly coupled type-II superconductor hosting eight pairs of WPs in the BZ with closed loops of surface Fermi arcs [47][48][49]. In light of the intriguing properties of CaSn 3 , investigation on the analogue BaSn 3 in terms of the electronic structure to examine possible nontrivial topological states is very valuable.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, superconducting compounds ASn 3 (A=Ca or Ba) were predicted to host topological semimetal states [58][59][60][61][62] . Studies on the topology in the weak coupling superconductor CaSn 3 propose that it hosts topological nodal-line semimetal states in the absent of spin-orbital coupling (SOC) and would evolve to Weyl nodes with SOC [58][59][60] . While, its relatively complicated band structure impedes the direct investigation of the nontrivial band topology therein.…”
Section: Introductionmentioning
confidence: 99%